Gleaning fishery of conch (Gastropoda strombidae) in seagrass beds of Guimaras Island, the Philippines - Diamante, Rose Ann M.; Monteclaro, Harold M.; Altamirano, Jon P.; Santander–de Leon, Sheila Mae S. (2025)
Gleaning is a subsistence fishery vital to the lives of coastal communities. The gastropod conch is among those found abundant in gleaners’ catch, particularly observed in Nueva Valencia, Guimaras, the Philippines. Three adjacent barangays with a wide expanse of seagrass intertidal area were studied for aspects of conch gleaning fishery through a structured questionnaire and the conduct of an actual catch survey. Results showed that conch gleaning is a secondary source of income (80%), mainly conducted by women (85%) during low tide. It contributes to their food consumption and additional income, where a kilo of conch is sold fresh and unprocessed at PHP 50–60, contributing to their monthly income at PHP 500–1000 maximum and PHP 100–200 minimum. Six species of conch were identified from the actual catch survey. Gleaning time ranges 2–4 h/d at 0.2–0.6 kg/h CPUE. An estimated 1,728–5,184 kg of conch, or around 180,000–550,000 individuals, may be exploited annually based on actual catch calculations. These levels of exploitation may pose a risk to the sustainability of the resource. An observed decline in the abundance of conch for the past 20 years, where management measures such as limitations on conch size and collection volume were indicated by the respondents. As an undocumented fishery in the Philippines, this study presented the importance of conch gleaning in the livelihood of coastal residents and may serve as vital information for fishery policy recommendations. This study also showed that the use of an actual catch survey, aside from a questionnaire, enhanced the data and earned better interpretation of results.
Keywords: Fishery management